2022
DOI: 10.1002/pan3.10304
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the COVID‐19 pandemic on the demand for different shades of green

Abstract: 1. COVID-19 has heightened the dependence of urban dwellers on cultural ecosystem services provided by urban green spaces (UGS), specifically in regard to the provision of recreational opportunities, and psychological and physical health benefits arising from their use.2. As different types and levels of cultural ecosystem services are provided by different types of UGS, people may seek out different UGS to satisfy personal needs over various phases of COVID-19 mobility restrictions imposed by cities.We report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Interactions with nature were a particularly important coping mechanism for many during this crisis, whether it was through walks in green spaces or provisioning of culturally important foods and medicines. However, once again, the focus of much of the research on COVID effects on CES have taken place mostly in the global North and wealthier countries (Grima et al 2020, Ugolini et al 2020, Yap et al 2022. Therefore, our call for increased attention to CES in the global South and across diverse ecosystems and communities remains important, and we hope that other researchers will take up this charge and expand the CES literature in new and diverse ways, contributing both to improved ecosystem management, as cultural practices are recognized for their value, and expanded appreciation of the multidimensional benefits provided to humans from CES.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions with nature were a particularly important coping mechanism for many during this crisis, whether it was through walks in green spaces or provisioning of culturally important foods and medicines. However, once again, the focus of much of the research on COVID effects on CES have taken place mostly in the global North and wealthier countries (Grima et al 2020, Ugolini et al 2020, Yap et al 2022. Therefore, our call for increased attention to CES in the global South and across diverse ecosystems and communities remains important, and we hope that other researchers will take up this charge and expand the CES literature in new and diverse ways, contributing both to improved ecosystem management, as cultural practices are recognized for their value, and expanded appreciation of the multidimensional benefits provided to humans from CES.…”
Section: Discussionmentioning
confidence: 99%
“…This is reinforced by another study carried out by Scotland's Nature Agency [18], which found that almost three-quarters (70%) of people felt that spending time outdoors within nature in 2020 helped them to de-stress, relax and unwind and 56% agreed that it improved their physical health [18]. During the peak of the pandemic, prolonged home confinement because of travel restrictions was a source of motivation that influenced city dwellers' behaviour and preference for parks and open spaces [19]. Several studies also reported a general increase in green space use during the pandemic [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Socially, problems such as economic depression and unemployment also occurred [ 68 , 69 ]. In particular, the COVID-19 has been dealt with particularly seriously in cities where the potential for exposure to the virus is high due to high population density [ 34 , 70 ]. As people’s gathering and movement were restricted, the stress and mental health problems of city residents were exacerbated.…”
Section: Discussionmentioning
confidence: 99%
“…As COVID-19 had unprecedented impacts on the global society, research regarding the importance of UGS during a pandemic has been actively conducted [ 32 , 33 , 34 , 35 , 36 ]. Nevertheless, survey-based research among urban residents is rarely utilized [ 37 ].…”
Section: Introductionmentioning
confidence: 99%